Preoperative beta blockade and severe intraoperative bradycardia in liver transplantation. Issue 12 (27th October 2018) - Fu, Hong; Sun, Kai; Li, Jun; Gong, Weiyi; Agopian, Vatche; Yan, Min; Busuttil, Ronald W.; Steadman, Randolph H.; Xia, Victor W.
Abstract: Nonselective Beta blockade (NSBB) is commonly prescribed for liver transplantation (LT) candidates, but its impact on intraoperative hemodynamics is not well understood. In this study, we investigated if preoperative NSBB was associated with severe bradycardia during LT and if severe intraoperative bradycardia was associated with 30‐day mortality. Adult patients undergoing LT between 2005 and 2014 were included. Propensity matching was used to control selection bias. Intraoperative hemodynamics were compared between patients with and without preoperative NSBB. Univariate and multivariate methods were used in statistical analysis. Of 1452 patients, 370 who received preoperative NSBB were matched in a 1:1 ratio with those who did not. Propensity matching eliminated all significant differences between the two groups. Patients who received preoperative NSBB had a significantly higher incidence of severe intraoperative bradycardia compared with the non‐BB group (9.6% vs 3.2%, P = 0.001, OR 2.95, 95% CI 1.42‐6.12, P = 0.004). Intraoperative hypotension and postreperfusion syndrome were not significantly different between the two groups. Severe intraoperative bradycardia was associated with increased 30‐day mortality. In conclusion, preoperative NSBB was associated with severe intraoperative bradycardia in LT. In patients who receive preoperative NSBB, severe intraoperative bradycardia should be closely monitored in LT. Further studies assessing safety of preoperative NSBB and intraoperative bradycardia in LT are warranted.